Development and Validation of Genotoxic Impurity in Esomeprazole Magnesium Trihydrate Active Pharmaceutical Ingredient by LC-MS/MS - Yelampalli, Suresh Reddy; Jagarlapudi, Venkata Shanmukha Kumar; Mallu, Useni Reddy (Indian Journal of Pharmaceutical Education and Research, 2019)
Objectives: A rapid, sensitive and selective analytical method has been developed and validated by liquid chromatography tandem Mass spectrometry (LC-MS/MS) for the quantification of traces of Cumene Hydroperoxide in Esomeprazole magnesium trihydrate active pharmaceutical ingredient. Materials and Methods: The chromatographic separation was carried out on a Develosil Phenyl phase-UG-5 150 x 4.6mm, 3μm column. The mobile phase consisting of 1% Ammonia solution buffer and acetonitrile, the flow rate was 0.9 mL/min with isocratic elution. Results: The retention time of Cumene Hydroperoxide was found 9.25 mins. The developed method was validated according to ICH guidelines. The system suitability was found 4.8% RSD and the linearity calibration curve was linear over the concentration range of 2.309 ppm to 12.747 ppm (r = 0.999). The intraday and inter-day precision (RSD %) was 2.1% and the obtained recovery (%) was at LOQ to 150% is in between 92.4% to 102.8% respectively. Conclusion: The low RSD values and high recoveries of the method confirms the suitability of the method for quantification of Cumene Hydroperoxide in Esomeprazole magnesium trihydrate API.
Keywords: LC-MS/MS; Esomeprazole magnesium trihydrate; Cumene Hydroperoxide; Method validation; ICH guidelines